2013
DOI: 10.5037/jomr.2013.4402
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Relationship of Lingual Nerve to the Region of Mandibular Third Molar

Abstract: ObjectivesThis study evaluated the relationship of the lingual nerve with the adjacent anatomical structures of the mandibular third molar region, influencing the dentist to be aware of the variability of these relationships.Material and MethodsSamples of 24 human corpse half-heads were selected and divided according with the presence or absence of the mandibular third molars. The lingual nerve (LN) was explored, showing its run from the oblique line until its crossing with the submandibular gland duct. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 28 publications
3
39
2
Order By: Relevance
“…Hölzle et al reported that SD runs deep in the floor of the oral cavity without a relationship with the LN in 11.8 % of the cases [12]. Al-Amery et al found that LN was passing below the SD before rising again toward the ventral surface of the tongue in 12 out of the 13 of the cases, in one case the relationship was similar with the findings of Hölzle et al [1,12,15].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Hölzle et al reported that SD runs deep in the floor of the oral cavity without a relationship with the LN in 11.8 % of the cases [12]. Al-Amery et al found that LN was passing below the SD before rising again toward the ventral surface of the tongue in 12 out of the 13 of the cases, in one case the relationship was similar with the findings of Hölzle et al [1,12,15].…”
Section: Discussionsupporting
confidence: 61%
“…This is known as the classical pattern of the nerve. Mendes et al found that this situation occurs in 62.5 % of the cadavers, in the remaining 37.5 % LN crosses above the duct [15]. Hölzle et al reported that SD runs deep in the floor of the oral cavity without a relationship with the LN in 11.8 % of the cases [12].…”
Section: Discussionmentioning
confidence: 98%
“…This nerve occasionally communicates with the inferior alveolar, auriculotemporal or the mylohyoid nerves, and then passes between the lateral and medial pterygoid muscles in the infratemporal fossa before proceeding anteriorly and inferiorly on the surface of the medial pterygoid muscle. It has been found to have variable relationships with the medial surface of the medial pterygoid muscle during its course [ 6 , 7 ]. The LN courses closer to the medial surface of the mandibular ramus until it is just a few millimeters below and behind the junction of the vertical and horizontal rami of the mandible [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It then courses along the periosteum on the medial surface of the mandible to lie opposite the posterior root of the lower third molar. Here, it is covered only by the gingival mucoperiosteum, which is closely bound to the lingual plate of the mandible for a distance of 28.17 mm [ 6 , 9 , 10 ]. It has been reported that in 20–62% of the time, the LN is in contact with the lingual cortical plate [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, accidentally displaced third molars may cause iatrogenic/traumatic neural injuries [9] and even temporomandibular joint pain and dysfunction [10]. The current literature reports the displacement of both maxillary and mandibular third molars.…”
Section: Discussionmentioning
confidence: 99%